Reply to comment by Iverson on "The reduction of friction in long runout landslides as an emergent phenomenon". Issue 11 (22nd November 2016) - Johnson, Brandon C.; Campbell, Charles S.; Melosh, H. Jay
Abstract: Here we address the comments by Iverson (2016) on our recent work concerning the reduction of friction in long runout landslides. Iverson (2016) questions the veracity of our models and suggests that high basal pore fluid pressure is the dominant mechanism reducing friction in long runout landslides. The main goal of our work was to elucidate the mechanism responsible for the apparent reduction of friction and long runout occurring in the landslide simulations of Campbell et al. (1995), which did not include an interstitial fluid. We found that the apparent reduction of friction in large slides could be explained by acoustic waves causing sliding to preferentially occur at pressures below the expected overburden, a mechanism reminiscent of acoustic fluidization. Such a mechanism is required to explain the long runout of dry landslides such as those on the Moon and other airless or waterless bodies. While our models provide no estimates of the effect of fluids on landslide runout, we have demonstrated a mechanism that increases runout distances that does not involve fluids. Key Points: We reply to comment by Iverson Extraterrestrial landslides clearly demonstrate that dry landslides have reduced friction Our work demonstrates a friction reduction mechanism that does not involve fluid